2017
DOI: 10.1093/ajh/hpx096
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal but not Diurnal Hypertension Is Associated to Insulin Resistance Markers in Subjects With Normal or Mildly Elevated Office Blood Pressure

Abstract: Nocturnal but not diurnal hypertension was related to higher levels of 3 insulin resistance markers in normotensive and untreated mildly hypertensive adults; this relationship seems partially independent of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Blood pressure varies diurnally, rising during the day and dipping at night. The loss of this pattern due to disrupted circadian rhythm is correlated with insulin resistance and cardiovascular disease [44, 45]. It is unclear why the current study found a significant association only between sleep timing and systolic blood pressure.…”
Section: Discussionmentioning
confidence: 79%
“…Blood pressure varies diurnally, rising during the day and dipping at night. The loss of this pattern due to disrupted circadian rhythm is correlated with insulin resistance and cardiovascular disease [44, 45]. It is unclear why the current study found a significant association only between sleep timing and systolic blood pressure.…”
Section: Discussionmentioning
confidence: 79%
“…38 Salazar et al reported that nocturnal, but not diurnal hypertension, was associated with insulin resistance in untreated normotensive and mildly hypertensive patients. 39 Yan et al showed that a reverse dipping BP pattern was independent predictor of lacunar infarction in hypertensive patients. 40 The authors did not separately investigate the effect of nocturnal BP, but only 24-h BP.…”
Section: Target Organ Damagementioning
confidence: 99%
“…Asimismo, otro mecanismo de la utilización de terapia antiretrovirales, sería a través de mecanismos relacionados al daño endotelial y marcadores metabólicos como insulinorresistencia 12---14 . Esto es consistente la demostración previa que la insulinorresistencia tiene mayor relación con la HTA nocturna que con la diurna 15 . Basados en estos supuestos; tanto la HTA nocturna aislada como la HTA sostenida, podrían aparecer Existen varias limitaciones en este estudio que deben ser reconocidas: Primero, la cohorte de individuos con VIH analizada es pequeña en comparación con estudios de riesgo cardiovascular sobre población general.…”
Section: Discussionunclassified